ANALYSIS OF COMMUNITY WILLINGNESS TO PAY FOR MANGROVE FOREST CONSERVATION IN PANTAI LANGO VILLAGE AND THE DETERMINANT FACTORS USING A PARAMETRIC APPROACH - Wina Feby Irawan; Wahyu Fahrizal; Heru Susilo (Universitas Mataram, 2025)
Mangrove forest conservation is a crucial measure to prevent further ecological degradation in mangrove ecosystems. Such efforts require substantial financial resources for both conservation activities and management operations. Therefore, this study aims to estimate the community’s Willingness to Pay (WTP) for mangrove forest conservation in Pantai Lango Village and to identify the factors influencing their WTP. The research employs purposive sampling for sample selection and utilizes a parametric analytical approach through a logistic regression model. The findings indicate that the average WTP derived from the logistic regression model is Rp 39,184.69 per person. Additionally, two variables are found to significantly influence the community’s WTP in Pantai Lango Village, namely the bid amount and income.